先化简再求值6a(1-a)-(3a-7)(-3a-7),其中2a+a^2=-2
2个回答
6a(1-a)-(3a-7)(-3a-7)
=6a-6a²+(3a)²-49
=3a²+6a-49
=3(a²+2a)-49
=3×(-2)-49
=-55
相关问题
先化简.再求值 7a(a+b)-3b(a+b)其中 a=2/7 b=2/3
先化简再求值:2(a+√3)(a-√3)-a(a-6)+6其中a=√(2)-1,
先化简,再求值:[(3a-7)^2-(a+5)^2]\(4a-24),其中a=50\1
1.先化简,再求值:6a²-[ a²+(5a²-2a)-2(a²-3a)] 其中
先化简,再求值:[(3a-7)2-(a+5)2]÷(4a-24),其中a=[1/50].
先化简,再求值:[(3a-7)2-(a+5)2]÷(4a-24),其中a=[1/50].
先化简,再求值:[(3a-7)2-(a+5)2]÷(4a-24),其中a=[1/50].
先化简,再求值:[(3a-7)2-(a+5)2]÷(4a-24),其中a=[1/50].
先化简,再求值:[a/a−3−a+6a2−3a+3a],其中a=[3/2].
(2005•柳州)先化简,再求值:(3a2-ab+7)-(5ab-4a2+7),其中a=2,b=[1/3].